Development of a chronology for open water reservoirs and subterranean cisterns in the Negev Highlands (Israel) using Optically Stimulated Luminescence : Construction - Utilization - Abandonment - Junge, Andrea; Justus Liebig University Giessen (My University, 2024)
Ancient open water reservoirs and subterranean cisterns are frequently occurring archaeological installations in drylands like the Negev Highlands, Israel. The former type are round open water reservoirs, which were dug into impermeable layers in foot slope areas and wadis. They may reach 10 m to 12 m in diameter and 4 m to 5 m in depth and were lined internally with unhewn stones and clay or marl that served as an aquiclude. In comparison, subterranean cisterns are rock-cut, excavated into soft limestone or chalk formations with a capacity of up to several hundred cubic meters. These two types of installations to collect and store water can sustain settlements, agriculture, and nomadic pastoralism under dry conditions. Despite the large number of cisterns and reservoirs in the Negev Highlands, they have scarcely been studied systematically.
Crucial for investigating water harvesting systems and their sediments is the establishment of robust chronologies of their life cycles. When the cisterns and water reservoirs are constructed, material is removed and deposited on an adjacent spoil pile. During precipitation events surface runoff from adjoining slopes erodes and transports sediments, which are then deposited in the reservoirs and cisterns. As long as they are maintained, the material is removed and also deposited on the spoil pile. After the cessation of maintenance, the installations were filled up with sediments.
The transport and deposition of sediments enables the application of optically stimulated luminescence (OSL) at the preferred dating method to determine the time of construction, utilisation and abandonment of reservoirs and cisterns. The interpretation of OSL ages is supported by micromorphological analyses and provides insights into the life cycles of the different installations, enabling a discussion about their chronology, the circumstance of construction and their purpose.
The age determinations of ten studied installations allow the conclusion that the open water reservoirs were introduced into the Negev Highlands latest during the Intermediate Bronze Age with a continuing construction until Medieval times, while the construction of subterranean cisterns started during the Roman period, without interrupting the construction of further reservoirs. From this, it can be derived that the construction of different types of water collection and storage systems occurred in different contexts. While the construction of reservoirs could be carried out by small groups in a relatively short time, the building of cisterns required more technological knowledge, more individuals, and longer periods, facilitated by central authorities.
Keywords: Israel; Cistern; Water reservoir; Optically stimulated luminescence; ddc:550; ddc:930